2021
DOI: 10.3233/hab-210442
|View full text |Cite
|
Sign up to set email alerts
|

Over-expression of IL-6 coding gene in the peripheral blood of migraine with aura patients

Abstract: Migraine is a common disorder which is placed among the top ten reasons of years lived with disability. Cytokines are among the molecules that contribute in the pathophysiology of migraine. In the current study, we evaluated expression levels of IL-6 coding gene in the peripheral blood of 120 migraine patients (54 migraine without aura and 66 migraine with aura patients) and 40 healthy subjects. No significant difference was detected in expression of IL-6 between total migraine patients and healthy controls (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…An investigation of the IL-6 coding gene in the peripheral blood of M0 and MA patients demonstrated no significant differences in the expression of IL-6 between total migraine patients and healthy controls. However, the expression of IL-6 was significantly higher in the MA patients versus the controls [ 177 ]. A clinical study investigating cytokine-coding gene expression in blood among M0 and MA patients revealed that the expression of IL-4, tumor growth factor-beta (TGF-beta), and TNF-alpha was increased in patients compared to that in controls, but there was no difference in the expression levels of IL-1beta, IL-17, and IL-2.…”
Section: Cytokine Function In Migraine and Neuropathic Painmentioning
confidence: 99%
“…An investigation of the IL-6 coding gene in the peripheral blood of M0 and MA patients demonstrated no significant differences in the expression of IL-6 between total migraine patients and healthy controls. However, the expression of IL-6 was significantly higher in the MA patients versus the controls [ 177 ]. A clinical study investigating cytokine-coding gene expression in blood among M0 and MA patients revealed that the expression of IL-4, tumor growth factor-beta (TGF-beta), and TNF-alpha was increased in patients compared to that in controls, but there was no difference in the expression levels of IL-1beta, IL-17, and IL-2.…”
Section: Cytokine Function In Migraine and Neuropathic Painmentioning
confidence: 99%
“…Investigation of the IL-6 coding gene in peripheral blood of M0 and MA patients demonstrated no significant differences in expression of IL-6 between total migraine patients and healthy controls. However, the expression of IL-6 was significantly higher in MA patients versus controls [124]. A clinical study investigating cytokinecoding gene expression in blood among M0 and MA patients revealed that the expression of IL-4, tumor growth factor-beta (TGF-beta) and TNF-alpha was increased in patients compared to controls, but there was no difference in expression levels of IL-1beta, IL-17 and IL-2.…”
Section: Migrainementioning
confidence: 99%
“…On the other hand, several studies reported that patients with various types of chronic headache have elevated levels of IL-6 [11] , [12] , [13] . High levels of IL-6 have even been considered a reliable way to measure intensity and impact of headache due to COVID-19 [14] .…”
Section: Evaluation Of the Hypothesismentioning
confidence: 99%